PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 63 PEKANBARU - Dian Purnama Sari; Zairul Antosa; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted because of low yield IV grade social studies student of SD Negeri 63 Pekanbaru, there were many 22 students that achieve criteria minimum were just 7 students (31,80 percen) while the student not able to achieve criteria minimum were 15 students. The purpose of this research to improve outcomes IPA Students class IV Negeri 63 Pekanbaru with implementation model learning cycle. Model learning cycle is learning that centered learning. Model learning cycle is a stage activiti that organized as well in other the learning can mastery competences that must be achieve in learning whit way that active. Design this research is action research classroom that each cycle consist of two meeting. The subject of this research is Students’ class IV Negeri 63 Pekanbaru with students’ total are 22 students that consist of 11 male students and 11 female students. Instrument that used in collecting the data of the research are observation sheet teacher activities and students activities then the students exam that conducted each of cycle to measure the improvement the student output. Percentage teachers’ activity after implemented model learning cycle of the first meeting teachers’ activity percentage is 55 percent whit category good and improve of the fourth meeting become 88 percent with category very good. Implementation model learning cycle can improve output of the student. It can see from base score UH I had improvement 4,60percent and from base score to UH II had improvement also 23,50 percent. The core can conclude that implementation model learning cycle can improve outcomes Students’ class IV Negeri 63 Pekanbaru.Keyword: Learning Cycle, Learning Outcomes IPA